Text network analysis of research topics and trends on global health nursing literature from 1974 ‐2017 - Lee, Soo‐Kyoung; Hong, Hye Sun (Journal of advanced nursing, 2021)
Aims The purpose of this study is to examine the relationship between keywords in existing global health nursing studies during 44 years (1974–2017) and to develop schematic diagrams of the relationship between these keywords from a macro perspective. It is to identify the trend of the literature in global health nursing field. Design A descriptive bibliometric analysis of publications in global health nursing. Methods The keywords from 7,115 articles and literatures were examined using the Text Rank Analyzer via the applied text network analysis with NetMiner 4.0. Results As for global health nursing, keywords with the most frequent appearance and the highest networking degree in centrality were ‘study’, ‘patient’, ‘nurse’, and ‘women’. Six central keywords were also found highly related to other keywords: ‘global health nursing’, ‘study’, ‘patient’, ‘care’, ‘nurse’, and ‘education’. By measuring the degree of keywords connected to other keywords in centrality, six clusters were established. Then, emerging topics assessed by time periods were identified as follows: the beginning phase (‘breastfeeding’, ‘women’, and ‘children’), the development phase (‘quality’, ‘life’, and ‘human immunodeficiency virus’), the maturation phase (‘mental health’, ‘depression’, and ‘global health’), and the expansion phase (‘pregnancy’, ‘palliative care’, and ‘infectious disease’). Conclusion The identified trends on this study will help nurse leaders to grasp the trends and insights for global health and to train future nurses to serve clients better in the practice fields. Impact Keywords with the highest appearance and centrality in the network were found in the global health articles. The bibliometric analysis showed various subjects according to the following phases: beginning development maturation and expansion. The awareness of the trend change in the global health helps nursing researchers and educators modify the curriculum of global health nursing and train future nurses to be equipped with the global health competencies. 摘要 目的 本研究旨在探讨44年来(1974年‐2017年) , 现有全球健康护理研究中不同关键词的相关性, 并从宏观角度绘制关键词相关性示意图。最终目的是了解全球健康护理领域文献的发展趋势。 设计 针对全球健康护理出版物进行描述性文献计量分析。 方法 通过NetMiner 4.0应用文本网络分析, 采用Text Rank分析法对7115篇文章和文献中的关键词进行分析。 结果 全球健康护理中, 最常出现且网络化程度最高的关键词为“研究”、“患者”、“护士”和“女性”。共六大中心关键词, 分别为: “全球健康护理”、“研究”、“患者”、“护理”、“护士”和“教育”, 并且, 此类关键词与其他关键词高度相关。目前, 通过计量上述关键词与其他关键词的关联度, 设立六大集群。随后,可根据时间段评估新兴主题, 具体如下: 开始阶段 (“母乳喂养”、“女性”和“儿童”) 、发展阶段 (“质量”、“生活”和“人类免疫缺陷病毒”) 、成熟阶段 (“心理健康”、“抑郁”和“全球健康”) , 以及扩张阶段 (“怀孕”、“姑息治疗”和“传染病”) 。 结论 现已确定本研究发展趋势, 有助于护士长掌握全球健康趋势和见解, 并为将来入职的护士提供培训, 以便其在实践过程中更好地为客户服务。 影响 网络中出现率和中心度最高的关键词均已收录于全球健康文章。文献计量学分析表明, 不同学科的发展都经历了以下阶段: 开始发展、成熟阶段和扩展阶段。全球健康趋势的变化的掌握有助于护理研究者和教育工作者变更全球健康护理课程, 并培养未来护士, 确保其具备全球健康维护能力。